The Influence of Islamic Service Quality and Trust on Customer Satisfaction and Intention in Reusing The Services in The Implementation of Umrah and Special Hajj Pilgrimage - Abdul Subhan; Achmad Firdaus Firdaus; Mukhamad Najib (Jurnal Ekonomi Syariah Teori dan Terapan, 2023)
ABSTRACT: Seeing the high potential for Umrah and Special Hajj departures, with a very large number of Umrah and Special Hajj travel, making competition between travel even higher.  This study aimed to determine the effect of Islamic service quality and trust on customer satisfaction, which will relate to interest in using it again. The method used in this research was the quantitative exploratory method. The participants in this study were Umrah and Special Hajj pilgrims who are registered with Hajj and Umrah organisers with official permits and domiciled in Java. The sampling technique in this study was probability random sampling with a total sample of 100 respondents. The analysis technique of the study was SEM-PLS  by using the SmartPLS 3.2.9 application. The results showed that the quality of Islamic services provided by the travel company and the trust of pilgrims have a significant influence on customer satisfaction felt by Umrah and Special Hajj pilgrims, which also affects their interest in reusing Umrah and Special Hajj services at the travel company. This research is very useful for Hajj and Umrah travel organisers in Indonesia in order to improve the quality of organising Hajj and Umrah for the comfort and solemnity of customers' worship. Keywords: Islamic Service quality, trust, service satisfaction, re-patronage Intention. ABSTRAK: Melihat tingginya potensi keberangkatan Umroh dan Haji Khusus, serta jumlah travel penyedia layanan tersebut yang sangat banyak, membuat persaingan antar travel semakin tinggi.  Penelitian ini bertujuan untuk mengetahui pengaruh kualitas pelayanan islami dan kepercayaan terhadap kepuasan pelanggan, yang akan berhubungan dengan minat pelanggan untuk menggunakan jasa dan layanan kembali. Metode yang digunakan dalam penelitian ini adalah metode eksplanatori kuantitatif. Partisipan dalam penelitian ini adalah jamaah umroh dan haji khusus yang terdaftar pada penyelenggara haji dan umroh yang memiliki izin resmi dan berdomisili di Pulau Jawa. Teknik pengambilan sampel dalam penelitian ini adalah probability random sampling dengan jumlah sampel sebanyak 100 responden. Teknik analisis dalam penelitian ini adalah SEM-PLS dengan menggunakan aplikasi SmartPLS 3.2.9. Hasil penelitian menunjukkan bahwa kualitas pelayanan islami yang diberikan oleh perusahaan travel dan kepercayaan jamaah memiliki pengaruh yang signifikan terhadap kepuasan pelanggan yang dirasakan oleh jamaah umroh dan haji khusus, yang juga berpengaruh terhadap minat mereka untuk menggunakan kembali jasa pelayanan umroh dan haji khusus pada perusahaan travel tersebut. Penelitian ini sangat bermanfaat bagi para penyelenggara perjalanan haji dan umroh di Indonesia dalam rangka meningkatkan kualitas penyelenggaraan ibadah haji dan umroh demi kenyamanan dan kekhusyukan ibadah pelanggan. Kata Kunci: Kualitas Pelayanan Islami, Kepercayaan, Kepuasan Pelanggan,  Minat menggunakan kembali jasa. REFERENCES Abdullah, A. A., Awang, M. D., & Abdullah, N. (2020). Islamic tourism: The characteristics, concept and principles. KnE Social Sciences, 196–215. doi:10.18502/kss.v4i9.7326 Abdullah, D., Hamir, N., Nor, N. M., Jayaraman, K., & Rostum, A. M. M. (2018). Food quality, service quality, price fairness and restaurant re-patronage intention: The mediating role of customer satisfaction. International Journal of Academic Research in Business and Social Sciences, 8(17), 211–226. doi:10.6007/IJARBSS/v8-i17/5226 Ahmad, A. R., Keerio, N., Jameel, A. S., & Karem, M. A. (2020). The relationship between national culture and succession planning in Malaysian public universities. Journal of Education and e-Learning Research, 7(3), 242–249. doi:10.20448/journal.509.2020.73.242.249 Al-Emran, M., Mezhuyev, V., & Kamaludin, A. (2018). PLS-SEM in Information Systems Research: A comprehensive methodological reference. Proceeding of International Conference on Advanced Intelligent System and Informatics 2018, 845, 644-653. doi:10.1007/978-3-319-99010-1_59 Ali, H. (2019). Building repurchase intention and purchase decision: Brand awareness and brand loyalty analysis (Case study private label product in Alfamidi Tangerang). Saudi Journal of Humanities and Social Sciences, 04(09), 623–634. doi:10.36348/sjhss.2019.v04i09.009 Becker, J. M., Cheah, J. H., Gholamzade, R., Ringle, C. M., & Sarstedt, M. (2022). PLS-SEM's most wanted guidance. International Journal of Contemporary Hospitality Management, 35(1)321–346. doi:10.1108/IJCHM-04-2022-0474 Belina, A., & Efendi, A. (2019). Word of Mouth, iklan, dan citra perusahaan terhadap keminatan konsumen travel Haji dan Umrah. Jurnal Perspektif Bisnis: Jurnal Ilmu Administrasi Bisnis, 37–46. BPS. (2022). Pada tahun 1443H/2022M, indeks kepuasan jemaah haji Indonesia (IKJHI) sebesar 90,45. Retrieved from https://www.bps.go.id/pressrelease/2022/12/19/1948/pada-tahun-1443h-2022m--indeks-kepuasan-jemaah-haji-indonesia--ikjhi--sebesar-90-45-.html Brady, M., & Robertson, C. (1999). An exploratory study of service value in the USA and Ecuador. International Journal of Service Industry Management, 10 (5), 469–486. doi:10.1108/09564239910289003 Buddy, Tabroni, & Salim, F. (2019). Pengaruh kualitas pelayanan dan kepercayaan terhadap kepuasan pelanggan dan dampaknya pada reputasi perusahaan (Studi empiris pada perusahaan travel Umroh dan Haji di Jakarta Timur). Ekobisman: Jurnal Ekonomi Bisnis Dan Manajemen, 4(2), 110–125. doi:10.35814/jeko.v4i2.1058 Choi, S. H. (2018). Impact on customer trust and customer satisfaction according to the logistics service quality of home shopping. International Journal of Pure and Applied Mathematics, 118(19), 277–289. Chulaifi, M., & Setuowati, F. (2018). Pengaruh kualitas pelayanan, persepsi harga dan kepercayaan terhadap kepuasan konsumen jasa travel Umrah dan Haji pada PT. Sebariz Warna Berkah di Surabaya periode 2017-2018. JHP17: Jurnal Hasil Penelitian, 3(1), 40-54. Cristescu, M. P., NeriÈ™anu, R. A., Flori, M., Stoica, F., & Stoica, F. L. (2021). Analysing the stock market as an economic lever, using a qualitative and a quantitative model. Mathematics, 9(19), 2369. doi:10.3390/math9192369 Dawi, N. M., Jusoh, A., Streimikis, J., & Mardani, A. (2018). The influence of service quality on customer satisfaction and customer behavioral intentions by moderating role of switching barriers in satellite pay TV market. Economics & Sociology, 11(4), 198-218. doi: 10.14254/2071789X.2018/11-4/13 Elpansyah, C., Nurdin, S., & Rahayu, Y. S. (2019). Pengaruh Word Of Mouth terhadap minat beli melalui citra perusahaan dan kepercayaan sebagai variabel intervening pada jasa Umroh PT Indojava Mulia Wisata. Jurnal Sains Manajemen, 1(1), 85–95. doi:10.51977/jsm.v1i1.94 Faza, H., & Widiyanto, I. (2016). Studi minat mereferensikan dalam jasa travel Umrah. Diponegoro Journal of Management, 5(1), 117–131. Hair Jr, J. F., Hult, G. T., Ringle, C. M., Sarstedt, M., Danks, N. P., & Ray, S. (2021). Partial least squares structural equation modeling (PLS-SEM) using R. Switzerland: Springer. Retrieved from https://link.springer.com/book/10.1007/978-3-030-80519-7 Hair Jr, J. F., Sarstedt, M., Hopkins, L. G., & Kuppelwieser, V. (2014). Partial least squares structural equation modeling (PLS-SEM) An emerging tool in business research. European Business Review, 26(2), 106-121. doi:10.1108/EBR-10-2013-0128 Hellier, P. K., Geursen, G. M., Carr, R. A., & Rickard, J. A. (2003). Customer repurchase intention: A general structural equation model. European Journal of Marketing, 37(11), 1762–1800. doi:10.1108/03090560310495456 Kotler, P., & Armstrong, G. (2004). Dasar-dasar pemasaran. Jakarta: Prenhallindo. Laely, N. (2016). Analisis pengaruh kepercayaan dan harga terhadap loyalitas pelanggan dimediasi kepuasan pada PT. Telkomsel di Kota Kediri. MM17: Jurnal Ilmu Ekonomi Dan Manajemen, 3(2), 61-74. doi:10.30996/jmm17.v3i02.802 Levine, J. H., Klein, A., & Mathews, J. (2001). Data without (operational) variables. Journal of Mathematical Sociology, 25(3), 225–273. doi:10.1080/0022250X.2001.9990253 Halomoan, M, E., Kumadji, S., & Yulianto, E. (2014). Pengaruh kualitas pelayanan terhadap kepuasan, kepercayaan dan loyalias (Survei pada Pelanggan yang menginap di Jambuluwuk Batu Resort Kota Batu). (Skripsi Sarjana, Universitas Brawijaya). http://repository.ub.ac.id/id/eprint/116736/ McKnight, D. H., Choudhury, V., & Kacmar, C. (2002). No title developing and validating trust measures for e-commerce: An integrative typology. Information Systems Research, 13(3), 334–359. doi:10.1287/isre.13.3.334.81 Othman, A., & Owen, L. (2001). The multi dimensionality of carter model to measure customer service quality (SQ) in Islamic banking industry: A study in Kuwait finance house. International Journal of Islamic Financial Services, 3(4), 1–12. Othman, B. A., Harun, A., De Almeida, N. M., & Sadq, Z. M. (2020). The effects on customer satisfaction and customer loyalty by integrating marketing communication and after sale service into the traditional marketing mix model of Umrah travel services in Malaysia. Journal of Islamic Marketing, 12(2), 363–388. doi:10.1108/JIMA-09-2019-0198 Othman, B., Harun, A., Rashid, W., & Ali, R. (2019). The impact of Umrah service quality on customer satisfaction towards Umrah travel agents in Malaysia. Management Science Letters, 9(11), 1763–1772. doi:10.5267/j.msl.2019.6.014 Phuong, N. N., & Dai Trang, T. T. (2018). Repurchase intention: The effect of service quality, system quality, information quality, and customer satisfaction as mediating role: a PLS approach of m-commerce ride hailing service in Vietnam. Marketing and Branding Research, 5(2), 78. doi:10.33844/MBR.2018.60463 Prasetyo, B. (2006). Metode penelitian kuantitatif teori dan aplikasi. Surabaya: Pustaka Pelajar. Sholihin, M., & Ratmono, D. (2021). Analisis SEM-PLS dengan WarpPLS 7.0. Yogyakarta: ANDI. Tate, R. L. (2010). A compendium of tests, scales and questionnaires: The practitioner's guide to measuring outcomes after acquired brain impairment. London: Psychology Press, Taylor & Francis Group. Wailmi, K., & Tamam, T. (2022). Tourism during covid 19: Service quality and location toward customer satisfaction. International Journal of Education and Social Science Research, 5(2), 355–363. doi:10.37500/IJESSR.2022.5222 Wang, K. Y. (2022). Sustainable tourism development based upon visitors' brand trust: A case of "100 Religious Attractions.” Sustainability, 14(4), 1977. doi:10.3390/su14041977 Yamin, S., & Kurnoawan, H. (2011). Generasi baru mengolah data penelitian dengan partioal least square path modeling. Jakarta"¯: Salemba Infotek. Yi, Y., & La, S. (2004). What influences the relationship between customer satisfaction and repurchase intention? Investigating the effects of adjusted expectations and customer loyalty. Psychology & Marketing, 21(5), 351–373. doi:10.1002/mar.20009 Zainal, V. (2017). Islamic marketing management: Mengembangkan bisnis dengan hijrah ke pemasaran Islami mengikuti praktik Rasulullah saw. Jakarta: Bumi Aksara.